2019
DOI: 10.2967/jnumed.118.220384
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal α-Emitting Radioimmunotherapy with 211At in Relapsed Ovarian Cancer: Long-Term Follow-up with Individual Absorbed Dose Estimations

Abstract: Eliminating microscopic residual disease with α-particle radiation is theoretically appealing. After extensive preclinical work with αparticle-emitting 211 At, we performed a phase I trial with intraperitoneal α-particle therapy in epithelial ovarian cancer using 211 At conjugated to MX35, the antigen-binding fragments-F(ab′) 2-of a mouse monoclonal antibody. We now present clinical outcome data and toxicity in a long-term follow-up with individual absorbed dose estimations. Methods: Twelve patients with relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…Among the α-emitters of interest for human use, 211 At is a main candidate and we have explored it continuously for clinical use in α-RIT of ovarian cancer [30][31][32]. Astatine-211 offers a theranostic approach to TAT since the decay involves the emission of K X-rays (77-93 keV) allowing for in vivo γ-quantification by planar and SPECT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Among the α-emitters of interest for human use, 211 At is a main candidate and we have explored it continuously for clinical use in α-RIT of ovarian cancer [30][31][32]. Astatine-211 offers a theranostic approach to TAT since the decay involves the emission of K X-rays (77-93 keV) allowing for in vivo γ-quantification by planar and SPECT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal radioimmunotherapy using 212 Pb conjugated to trastuzumab, an α-emitter, in a first-inhuman study was found to be safe with patients showing a trend of decreasing tumor growth and blood-based biomarkers with increasing administered radioactivity (33). In another study Hallqvist et al, investigated intraperitoneal α-particle therapy using MX35, the antigen-binding fragments-F(ab ′ )2-of a mouse monoclonal antibody, conjugated with α-emitter 211 At in epithelial ovarian cancer patients (35). MX35 F(ab ′ )2 fragment targets the cell surface glycoprotein NaPi2b (SLC34A2) that is expressed on more than 90% of human epithelial ovarian cancers (74).…”
Section: Her2mentioning
confidence: 99%
“…Since this clinical study, not many more reports were published. In 2009, one additional study reports on [ 211 At]At-MX35 F(ab') 2 for the treatment of ovarian cancer with a long-term follow-up presented most recently [62,63]. In contrast to Zalutsky et al, another group reported on 211 At-labelling via a direct procedure on an ε-lysyl-3-(trimethylstannyl)benzamide modified immunoconjugate [64].…”
Section: Astatinementioning
confidence: 99%